2013
DOI: 10.1002/chem.201303343
|View full text |Cite
|
Sign up to set email alerts
|

Nanosheet‐Stacked Chiral Silica Transcribed from Metal Ion‐ and pH‐Tuned Supramolecular Crystalline Complexes of Polyamine‐D‐Glucarate

Abstract: D-glucaric acid (D-Glc) associates with linear poly(ethyleneimine) (PEI) through hydrogen bonding and electrostatic interactions in aqueous media to form nanostructured crystalline PEI/D-Glc/H2O complexes with PEI/D-Glc/H2O ratios of 2:1:2. These complexes can serve as templates for silica depositions from hydrolytic condensation of tetramethoxysilane to guide morphologically duplicated silica under very mild conditions. Their microscale morphologies are tunable by use of the crystalline complexes regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…[27] Furthermore,w ea lso presented af acile strategy to fabricate chiral silica materials using av ery effective catalytic template component formed by crystallization-driven self-assembly of linear PEI with chiral acids such as tartaric acid and d-glucarate in water. [28,29] In this system,t he carboxyl groups of chiral acids are well associated with basic secondary amino groups of PEI polymer chain in a1 :1 molarr atio to form chiral crystalline complexes.T hese chiral complexes play ad ual role in the fur-ther silicification process. They not only direct silicad eposition as templates, but also promote the hydrolytic condensation of silica precursors withouta dditional catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Furthermore,w ea lso presented af acile strategy to fabricate chiral silica materials using av ery effective catalytic template component formed by crystallization-driven self-assembly of linear PEI with chiral acids such as tartaric acid and d-glucarate in water. [28,29] In this system,t he carboxyl groups of chiral acids are well associated with basic secondary amino groups of PEI polymer chain in a1 :1 molarr atio to form chiral crystalline complexes.T hese chiral complexes play ad ual role in the fur-ther silicification process. They not only direct silicad eposition as templates, but also promote the hydrolytic condensation of silica precursors withouta dditional catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…We found that PEI interacted with guest chiral tartaric acid or glucaric acid in a 1:1 molar ratio of NH/COOH to form nanoscale crystalline complexes, which exhibited evident CD activity in solid state 55. 56 We employed chiral or racemic crystalline complexes consisting of linear PEI and chiral D ‐, L ‐, and dl ‐tartaric acid as templates to deposit silica in the same way as we did in the PEI/water system. Expectedly, all templates easily produced silica hybrids SiO 2 /PEI@ D , SiO 2 /PEI@ L and SiO 2 /PEI@ dl under very mild conditions of ambient temperature, nearly neutral aqueous medium and short reaction time 55.…”
Section: Chiral Templates For Transcribing Chirality Into Silica Matementioning
confidence: 99%
“…Replacing the chiral source of tartaric acid by D ‐glucaric acid, we also developed chiral crystalline complexes consisting of PEI and D ‐Glc (PEI/ D ‐Glc) and used this complex as catalytic template in the hydrolytic condensation of TMOS (Figure 36). Interestingly, the complex PEI/ D ‐Glc showed nanosheet structures with crystallites and promoted the silicification of TMOS to direct chiral silica with nanosheet‐stacked morphology 56. Tuning the formation conditions of the template of PEI/ D ‐Glc by pH and metal ions, such as Ca 2+ , Zn 2+ , Mg 2+ , we controlled the silica nanosheet array with spherical or twisted structures (Figure 37).…”
Section: Chiral Templates For Transcribing Chirality Into Silica Matementioning
confidence: 99%
See 2 more Smart Citations